2012
DOI: 10.1007/s11916-012-0280-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Perimenstrual Migraine with Triptans: an Update

Abstract: Pure menstrual migraine (PMM) and menstrually related migraine (MRM) are difficult challenges in migraine management. Triptans are a class of highly selective serotonin receptor agonists, which interfere with the pathogenesis of migraine and are effective in relieving the associated neurovegetative symptoms. In recent years triptans have been extensively proposed for the treatment of severe, disabling, and recurrent perimenstrual migraine attacks. This review summarizes the different levels of recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…Clinical studies also show the possibility of a short-term prevention of perimenstrual migraine with triptans or hormonal treatment [7, 8]. Recently, non-invasive vagus nerve stimulation has been suggested as prophylactic treatment for menstrual (related) migraine [9].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies also show the possibility of a short-term prevention of perimenstrual migraine with triptans or hormonal treatment [7, 8]. Recently, non-invasive vagus nerve stimulation has been suggested as prophylactic treatment for menstrual (related) migraine [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although all triptans have the same mechanism of action and simple and consistent pharmacokinetic features, there are specific differences among individual agents that may account for their different clinical attributes. For instance, in the treatment of perimenstrual migraines, which are known to be particularly severe and disabling, the different triptans showed different profiles of efficacy, either given for acute attacks or for short-term prophylaxis [35]. In the patient preference head to head comparative trials, the drugs showed similar efficacy in the short-term, in particular at 2 hours, but frovatriptan provided a more sustained response, with a lower recurrence rate, likely related to its much longer elimination half-life [6].…”
Section: Discussionmentioning
confidence: 99%
“…A reasoned guide useful to deal with pure MM should foresee the use of daily triptans during the bleeding phase for at least 3 days [8,9]. In case of migraine with MM days this approach is not useful as it could expose the patient to a situation of acute overuse, which occurs when the 10 days/month is reached with triptans single use or combined with NSAIDs.…”
Section: Bodymentioning
confidence: 99%